Bodily Practices and Subjectivities of Lao Migrant Female Sex Workers in a Thai Border Town - Chaimala, Theeraporn; Boonmongkon, Pimpawun; Thaweesit, Suchada; Singkul, Nattawut (Journal of Population and Social Studies [JPSS], 2026)
This study examines the bodily practices of Lao female sex workers in a Thai border town, focusing on how these practices are shaped by subjectivity and negotiated within a context of transnational mobility and legal ambiguity. Employing a qualitative research methodology, the study draws on in-depth and narrative interviews, as well as participant observation, with 20 Lao women. Findings show that bodily practices—such as cosmetic surgery, skin whitening, and emotional labor—are strategies of negotiation and identity-making within the ambiguities of borderland sex work. By foregrounding the body as a site of negotiation and agency, this study contributes to scholarship on migration and gender studies by illustrating how bodily practices serve as proactive tools for self-fashioning and agency within the complexities of borderland sex work.